Degrowth a vocabulary for a new era - D'Alisa, Giacomo; Demaria, Federico; Kallis, Giorgos (Routledge, Taylor & Francis Group, 2015)
"We live in an era of stagnation, rapid impoverishment, rising inequalities, and socio-ecological disasters. In the dominant discourse, these are effects of economic crisis, lack of growth or underdevelopment. This book argues growth is the cause of these problems and that it has become uneconomic, ecologically unsustainable and intrinsically unjust"-- Provided by publisher